(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Gofar N, Nur TP, Permatasari SDI, Muslimah S, Fikri H, Haryono A, Pujiati, Utami HA. 2023. Application of organic fertilizer enriched with Trichoderma harzianum on shallot (Allium cepa) cultivation in ultisols. Biodiversitas 24: 2426-2433. Shallot is a critical commodity with substantial economic value. However, several factors, such as pests and diseases, negatively impact its low productivity. Therefore, to address these challenges, the agricultural sector is developing an organic fertilizer enriched with the biological agent Trichoderma harzianum. This biological agent improves soil fertility, controls Fusarium wilt, and enhances shallot production. This study aimed to evaluate the effectiveness of organic fertilizer enriched with Trichoderma harzianum in suppressing the growth of Fusarium oxysporum and increasing shallot production. Therefore, it included five treatments of organic fertilizer enriched with Trichoderma harzianum at varying concentrations of 0, 200, 300, 400, and 500 kg ha-1. The results showed that applying 400 kg ha-1 organic fertilizer enriched with Trichoderma harzianum suppressed the Fusarium wilt. The dose of 500 kg ha-1 had the highest pH value of 5.50-5.78 among other treatments and increased 55.7% shallot production on Ultisols compared to the application of NPK 16-16-16. Based on these results, organic fertilizer enriched with Trichoderma harzianum could improve soil fertility, increase production and control the Fusarium wilt on shallot.